Evaluation of the learning environment and the perceived weakness of the curriculum: student perspective - Ahmed, Yasar; Taha, Mohamed H.; Alneel, Salma; Gaffar, Abdelrahim M. (International Journal of Research in Medical Sciences, 2018)
Background: Educational environment has been shown to have influence on learning outcome and affects student achievement, satisfaction, and success. The study was conducted to assess medical students’ perception of their learning environment and to explore areas of weakness within the educational environment. Methods: A mixed method of study, was performed using non-probability sampling at the Faculty of Medicine, Gezira University (FMUG), Sudan. An updated Arabic Dundee Ready Education Environment Measure (DREEM) was developed and administered to 854 students during the academic year 2016-2017. Results: Seventy five percent of students completed the inventory (638/854) and Sixty four percent (546/854) responded to the open-ended question providing comments and suggestions. The overall reliability coefficient alpha in this study was 0.914. The global score for this study was found positive (122/200). Students were most satisfied with the learning aspects, academic environment, and academic self-perception. However, they were unsatisfied with their teaching and social atmosphere (inadequate social support for stressed students, substandard teaching, overemphasised factual learning, unpleasant accommodation). The qualitative content analysis was performed and emerged with four themes: the physical environment, a number of students, pedagogical approaches and faculty-student communication. Conclusions: The study suggested the overall students’ perceptions of the educational environment in the FMUG were on the positive side. However, certain specific elements of the learning environment and educational programme need to be critically investigated and remedied. The updated Arabic DREAM can be used reliably in the context of medical education in Arabic speaking countries.